Innovative Analysis of Service-Learning Effects in Physical Education: A Mixed-Methods Approach - Capella-Peris, Carlos; Gil-Gomez, Jesús; Chiva-Bartoll, Òscar (Journal of teaching in physical education, 2020)
Purpose: To compare the development of teaching competency in preservice teachers of physical education (n = 96) through two different modalities of intervention from the same service-learning program. The preservice teachers provided a direct service to children with motor functional diversity, promoting their motor skills and counteracting their lack of social attention. Method: The topic was approached using mixed methods with methodological triangulation. Quantitative evidence was gathered through a quasi-experimental design of two nonequivalent experimental groups implementing the following instrument: "The Teaching Competency while performing Motor Skills and Body Language Games Rubric." Meanwhile, qualitative analysis was undertaken by elaborating upon 12 life histories of multiple crossed stories. Results: The quantitative results provided significant evidence regarding the academic effect of service-learning on preservice teachers, while the qualitative interpretation complemented this view, reflecting on how this learning was developed. Discussion/Conclusion: The authors provided the original findings of the service-learning effects on the teaching competency of preservice teachers as well as the promotion of additional academic and social learning.